2017
DOI: 10.1111/1745-9125.12164
|View full text |Cite
|
Sign up to set email alerts
|

Racial Discrimination, Racial Socialization, and Crime Over Time: A Social Schematic Theory Model

Abstract: Recent studies evince that interpersonal racial discrimination (IRD) increases the risk of crime among African Americans and familial racial socialization fosters resilience to discrimination's criminogenic effects. Yet, studies have focused on the short‐term effects of IRD and racial socialization largely among adolescents. In this study, we seek to advance knowledge by elucidating how racialized experiences—in interactions and socialization—influence crime for African Americans over time. Elaborating Simons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 130 publications
(195 reference statements)
1
33
0
Order By: Relevance
“…For example, in Code of the Street , Elijah Anderson (1999) indicated that residents of disadvantaged neighborhoods tend to adopt the norms of the street code subculture to handle their everyday routines. Studies of African Americans have also highlighted cultural promotive and protective factors (e.g., cultural pride, spiritually, and cultural socialization) among African American neighborhoods and cultures and its protective role in the face of adversities and stressors (Burt, Lei, & Simons, 2017; Causadias, 2013; Constantine, Donnelly, & Myers, 2002; Gaylord-Harden, Burrow, & Cunningham, 2012). …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in Code of the Street , Elijah Anderson (1999) indicated that residents of disadvantaged neighborhoods tend to adopt the norms of the street code subculture to handle their everyday routines. Studies of African Americans have also highlighted cultural promotive and protective factors (e.g., cultural pride, spiritually, and cultural socialization) among African American neighborhoods and cultures and its protective role in the face of adversities and stressors (Burt, Lei, & Simons, 2017; Causadias, 2013; Constantine, Donnelly, & Myers, 2002; Gaylord-Harden, Burrow, & Cunningham, 2012). …”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that individuals residing in socio-economically disadvantaged neighborhoods are exposed to a constellation of social stressors associated with increased presence of social disorder and subculture (Anderson, 1999; Burt, Lei, & Simons, 2017; Hill et al, 2005; Latkin & Curry, 2003; Ross & Mirowsky, 2009). These conditions foster concerns about safe and feelings of powerlessness and social isolation (Ross, 2011).…”
mentioning
confidence: 99%
“…Most prior studies on discrimination and crime make the implicit assumption that it is the amount of discrimination experienced or perceived that matters rather than specific subdomains that comprise most measures of discrimination (Bastos et al 2010). For example, much of the prior research on discrimination and crime primarily focus on African American experiences and use data from the Family and Community Health Study (FACHS; Brody et al 2006; Brody, Kogan, and Chen 2012; Burt, Lei, and Simons 2017; Burt and Simons 2015; Burt et al 2012; Evans, Simons, and Simons 2016; Gibbons et al 2004; Simons and Burt 2011; Simons et al 2003) or the Project on Human Development in Chicago Neighborhoods Study (PHDCN; Riina et al 2013; Unnever, Cullen, and Barnes 2016a, 2016b). The FACHS study used an adapted version of the Schedule of Racist Events (Landrine and Klonoff 1996), which focuses on how often participants perceived a variety of discriminatory experiences from global sources (e.g., how often has someone).…”
Section: Context Of Discriminationmentioning
confidence: 99%
“…Although they face criticism, some criminologists still fault the Commission's () position because they believe that biological or psycho‐biological differences are at the heart of the causes of crime (Mednick and Volavka, ; Wilson and Herrnstein, ). At the polar opposite view are those who argue that the differences are brought on by continued racism and discrimination in the United States (Burt, Lei, and Simons, , ; Unnever and Gabbidon, ). We believe that it is accurate, based on the weight of the research evidence, to state that most criminologists support the notion that, just as members of the Commission thought 50 years ago, research findings now indicate that Black–White differences in rates of criminal involvement can be explained by social and economic disadvantage (Morenoff, ).…”
Section: What Have We Learned About Race and Crime In The Past 50 Years?mentioning
confidence: 99%